A list of praying mantids (Mantodea, Insecta) of Vietnam - Thinh, Ta Huy (Academia Journal of Biology, 2012)
The mantids were collected by net and light trap from defferent localities in Vietnam during the period from 2000 to warch 2010. The Giglio - Tos & Beier classification of Mantodea was applied for identifying collected mantid specimens. Deposited in Institute of Ecology and Biological Resources (IEBR). A total of 50 Identified mantid species belong to 31 genera of two families Hymenopodidae (12 species) and Mantidae (38 species). In spite of the widespread species Mantis religiosa, all mantids collected are of Oriental fauna. Among 50 recorded species, 16 species are widespread in Oriental Region, 14 species distributed in range of Indian - Indochina - Malaya peninsula and South East Asian archipelagos, 10 species  were distributed spread in South China area and 10 ones were only recorded in Vietnam. This paper deals with 18 new records for Vietnam, namely Theopropus elegans, Acromantis formosana, Acromantis indica, Odontomantis monticola, Theopompa servillei, Toxodera denticulata, Paratoxodera meggitti, Haania doroshenkoi, Haania vitalisi, Gimantis authaemon, Gonypeta brigittae, Bimantis malaccana, Deiphobe incisa, Deiphobe yunnanensis, Tenodera fasciata, Rhombodera basalis, Rhombodera valida and Hierodula membranacea.